(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: As registration of birth is still extremely incomplete in India and many times real age is concealed with various intentions, doctors are called to opine about the age. Determination of the age of an individual from the appearance and the fusion of the ossification centers is a well-accepted fact in the field of medical and legal professions. Methodology: This observational study was conducted after taking Institutional ethics committee approval to conduct the study. This study comprised of a total number of 226 subjects, of which 131 (57.96%) were males and 95 (42.04%) were females, aged between 12- 24 years. Digital X-Rays (Antero- posterior view) of pelvis were taken after taking informed consent. Results: Average age of appearance of the ossification centre of iliac crest is 14 – 15 years in girls and 16 - 18 years in boys. Average age of fusion of iliac crest is 19 - 20 years in girls and 20 -21 years in boys. Average age of appearance of the ossification centre of ischial tuberosity is 15 -17 years in girls and 16 - 17 years in boys. Average age of fusion of ischial tuberosity is 20 - 21 years in both girls and boys. Conclusion: It is of paramount importance to correlate age in this particular age group with appearance and fusion of iliac crest & ischial tuberosity, as it acts as supporting parameter in establishing the age of an individual above age of 14 to 21 years.